Development Of Learning Media For The Formation Of Characteristics Based On The Philosophy Of Science - Jimi Asmara; Siti Masitoh; Mochamad Nursalim (Institute of Computer Science (IOCS), 2022)
Teachers tend to have different characteristics in delivering the material, which may result in different interpretations in the student's point of view. Learning media can be created using writing, audio, visual, or even a combination of all of them. If the selection of learning media is carried out correctly, it will greatly help the interaction in learning activities in the classroom. The philosophy of science and education has a great role in shaping the characteristics of learning media . In the philosophy of science and education, there are several aspects and dimensions that are the basis for making learning media, namely aspects of ideas and facts, as well as abstract and concrete dimensions both theoretically and practically. The approach of philosophy of science and education ontologically, epistemologically, and axiologically in the development of learning media, if summarized in accordance with its practical objectives, will be able to form practical values that lead to learning abilities or outcomes.